Testing the Efficacy of INSIGHTS on Student Disruptive Behavior, Classroom Management, and Student Competence in Inner City Primary Grades - McClowry, Sandra Graham (School mental health, 2009)
A prevention trial tested the efficacy of INSIGHTS into Children’s Temperament as compared to a Read Aloud attention control condition in reducing student disruptive behavior and enhancing student competence and teacher classroom management. Participants included 116 first and second grade students, their parents, and their 42 teachers in six inner city schools. Teachers completed the Sutter-Eyberg Student Behavior Inventory (SESBI) and the Teacher’s Rating Scale of Child’s Actual Competence and Social Acceptance (TRS) at baseline and again upon completion of the intervention. Boys participating in INSIGHTS, compared with those in the Read Aloud program, showed a significant decline in attentional difficulties and overt aggression toward others. Teachers in INSIGHTS, compared to those in the attention control condition, reported significantly fewer problems managing the emotional-oppositional behavior, attentional difficulties, and covert disruptive behavior of their male students. They also perceived the boys as significantly more cognitively and physically competent